Study of serum electrolytes with different clinical co-morbidities in complicated severe acute malnutrition children aged 6 months to 5 years - Meena, Suresh K.; Suman, Rameshwar L.; Jain, Rupali; Meena, Pradeep (International Journal of Contemporary Pediatrics, 2017)
Background: Severe acute malnutrition (SAM) is one of the most common health problem. SAM children are more prone to severe infections that culminates into different co-morbid conditions and consequentially leads to electrolyte derangements. Hence this study aims to find out the incidence of dyselectrolytemia (Na+ and K+) in malnourished children with different clinical co-morbid conditions. Methods: It was a hospital based prospective, case-control study conducted on 100 children of complicated as study group and 50 children of uncomplicated SAM as control group, over a period of six months in year 2016. The children included as per WHO reference criteria of SAM in 6 months to 5-years age group. All the enrolled children were assessed with detailed clinical examination according to different co-morbidities, including anthropometry and routine investigations along with serum electrolytes (Na+ and K+) and chest x-ray. Results: In our study, out of 100 complicated SAM children, dyselectrolytemia was present in 94.0% children. The SAM children with most co-morbidities had subnormal sodium ranging from 128-135 mEq/L while potassium was normal ranging from 3.68-4.34 mEq/L at the time of admission. We observed that mean sodium level was 131.82±6.66 mEq/L while mean potassium level was 4.17±1.03 mEq/L in complicated SAM children. In control group children mean sodium level was 135.90±4.26 mEq/L while mean potassium level was 4.14±1.11 mEq/L. Conclusions: To conclude that dyselectrolytemia is high in complicated SAM and it is mainly sodium disturbances in the form of hyponatremia in different co-morbid conditions. Hence, we recommend that due care is to be given for management of dyselectrolytemia in complicated SAM children.